Agreement between Heart Failure Patients and Their Primary Caregivers on Symptom Assessment - Hassan Sharifi; Mohammad Ali Rezaei; Nastaran Heydari Khayat; Neda Mohammadinia (Shiraz University of Medical Sciences, 2018)
Background: To decrease the readmission rate of heart failure (HF) patients, patients and their caregivers (CGs) should participate in symptoms assessment. This study aimed to assess the agreement between HF patients and their CGs on symptoms assessment. Methods: Using a correlational design, 100 HF patients with their CGs (100 dyads) were recruited from Department of Cardiology, Iranshahr, during August-December 2014. Data were collected using modified Heart Failure Symptom Survey (HFSS).Pearson and intra-class correlation coefficients (ICC) were used to analyze the degree of agreement within HF dyads, using SPSS16. The level of significance was set at 0.05. Results: The most frequent and severe symptom assessed equally by partners was shortness of breath (SOB). Dyads had a good agreement on assessment of extremity swelling (r=0.87, P≤0.01, ICC=0.861 CI: 0.798-0.901), SOB at rest (r=0.83, P≤0.01, ICC=0.775, CI: 0.680-0.845), SOB with activity (r=0.81, P≤0.01, ICC=0.795 CI: 0.711-0.858), and feeling depressed (r=0.77, P≤0.01, ICC=0.769, CI: 0.675-0.838). 28.6% of HF dyad had a good, 50% had a moderate, and 21.4 % had a poor agreement in assessment of HF symptoms. Conclusion: Most of the HF dyad members did not agree with each other on the assessment of symptoms. Knowledge, skills and ability of each dyad in HF symptoms assessment should be included in the patients' discharge planning and nurses must modify their misunderstanding or inability.